Aging increases proprioceptive error for a broad range of movement speed and distance estimates in the upper limb - Tulimieri, Duncan Thibodeau; Semrau, Jennifer A. (Frontiers in Human Neuroscience, 2023)
Previous work has identified age-related declines in proprioception within a narrow range of limb movements. It is unclear whether these declines are consistent across a broad range of movement characteristics that more closely represent daily living. Here we aim to characterize upper limb error in younger and older adults across a range of movement speeds and distances. The objective of this study was to determine how proprioceptive matching accuracy changes as a function of movement speed and distance, as well as understand the effects of aging on these accuracies. We used an upper limb robotic test of proprioception to vary the speed and distance of movement in two groups: younger (n = 20, 24.25 ± 3.34 years) and older adults (n = 21, 63 ± 10.74 years). The robot moved one arm and the participant was instructed to mirror-match the movement with their opposite arm. Participants matched seven different movement speeds (0.1 -0.4 m/s) and five distances (7.5 -17.5 cm) over 350 trials. Spatial (e.g., End Point Error) and temporal (e.g., Peak Speed Ratio) outcomes were used to quantify proprioceptive accuracy. Regardless of the speed or distance of movement, we found that older controls had significantly reduced proprioceptive matching accuracy compared to younger control participants (p  0.05). When movement speed was varied, we observed that errors in proprioceptive matching estimates of spatial and temporal measures were significantly higher for older adults for all but the slowest tested speed (0.1 m/s) for the majority of parameters. When movement distance was varied, we observed that errors in proprioceptive matching estimates were significantly higher for all distances, except for the longest distance (17.5cm) for older adults compared to younger adults. We found that the magnitude of proprioceptive matching errors was dependent on the characteristics of the reference movement, and that these errors scaled increasingly with age. Our results suggest that aging significantly negatively impacts proprioceptive matching accuracy and that proprioceptive matching errors made by both groups lies along a continuum that depends on movement characteristics and that these errors are amplified due to the typical aging process.